Sārtha Āyurvedīya hitopadeśa - Desāī, Raṇajitarāya, 1910- (Śrī Baidyanātha Āyurveda Bhavana, 1955)
Selections from various ancient treatises, with commentary, on the Ayurveda system in Indic medicine; critical edition.